Webometric Analysis of Indian State Tourism Websites - Singh, Ekta; P.S, Sibi (Journal of Data Science, Informetrics, and Citation Studies)
Official state tourism websites serve as primary sources of information for travelers. The digital presence maximizes their online visibility, provides appealing and uplifting content, and optimizes their online presence. Despite numerous studies on website usability and interaction features, a gap remains in comprehensively evaluating the state tourism websites in India. To analyze all 28 Indian state tourism websites, the current study utilizes webometric tools to collect data. The analysis incorporates metrics such as domain authority, page authority, Simple Web Impact Factor (SWIF), Google page rank, language accessibility, and social media presence. The results indicate substantial variation in website performance despite the widespread use of similar domain extensions, suggesting an overall homogeneity in URL structure but divergence in digital strength. Overall, the results demonstrate that the state's capacity to market and promote tourism in the digital age is closely tied to its online presence and multilingual accessibility. Lastly, the study highlights the practical and theoretical implications.
Keywords: Webometrics; Websites; Tourism; Web Impact Factor; Destination Management Organizations (DMO).